Validasi Generic Scale of Phubbing (GSP) Versi Bahasa Indonesia dengan Rasch Model - Isrofin, Binti (Universitas Nusantara PGRI Kediri, 2020)
This research aims to validate the Indonesian version of the Generic Scale of Phubbing (GSP) using the Rasch Model. Indicator of Phubbing is (1) Nomophobia, (2) Interpersonal conflict, (3) Self Isolation, and (4) Problem Acknowledgement. The research sample of 379 UNNES students consisted of 106 men and 273 women taken randomly from 8 faculties. The results of this study indicate that the Generic Scale of Phubbing has a respondent reliability index (α = 0.07), item reliability (α = 1.00). Based on these findings, the GSP instrument can be used to measure phubbing behavior for students. To get broader benefits, the use of GSP needs to be followed up by continuing development both in terms of writing statement items, number of statement items, the content of statements to the subject used in accordance with Indonesian culture.